Malignant melanoma revealed by testicular metastasi. (2015) - Dusaud, Marie; Adjadj, Lucille; Debelmas, Alexandre; Souraud, Jean Baptiste; Durand, Xavier
Highlights: Testicular tumor epidemiology after 65 years old is different than in young adult. Testicular metastasis of malignant melanoma is rare. Testicular metastasis of a malignant melanoma demonstrate the severity of the disease. Abstract: We report the case of an 83 years old man supported for painless indurated and nodular lesion of the left testicle. Histological analysis identified a primary cutaneous melanoma metastasis although it has never been found on physical examination. The discovery of a testicular mass should suggest first a germ cell tumor, despite in some populations (age over 60 years), other diagnosis are more frequent, including metastasis. Due to rapid disease progression and high mortality rate within a short interval, a complete staging looking for other secondary locations must be done and a multidisciplinary care and palliative involvement must also be initiated in the context of metastatic melanoma.